Nanotechnologies in food - Chaudhry, Qasim; Castle, L.; Watkins, Richard, Dr (RSC nanoscience & nanotechnology ;, 2010)
Recent developments in the field of nanotechnology have paved the way for lots of innovation in a number of industrial and consumer sectors, including food and food packaging. Whilst nanofood sector is a relatively new emergent, it is widely expected to grow rapidly in the future. A number of nano-sized additives and supplements for food and healthfood products, and nanotechnology derived food packaging materials, are already available in some countries, and their number is expected to increase in the coming years. Whilst such developments offer enormous benefits to the food sector, they have.